Penggunaan pupuk cair bioboost pada tanaman cabai (Capsicum annuum L. ) - JoÃ£o Da Silva Carvalho; Anak Agung Ngurah Mayun Wirajaya; Made Sri Yuliartini; Yohanes Parlindungan Situmeang (GEMA AGRO, 2018)
The purpose of this study was to determine the effect of bioboost liquid fertilizer concentration on the growth and yield of large chili plants. This research is a one-factor experiment using a simple randomized block design. The tested treatment is the Bioboost concentration at 8 levels, namely: B0 = 0 cc.l-1 (control), B1 = 5 cc.l-1, B2 = 10 cc.l-1, B3 = 15 cc.l-1, B4 = 20 cc.l-1, B5 = 25 cc.l-1, B6 = 30 cc.l-1, B7 = 35 cc.l-1. Giving liquid bioboost fertilizer to chili plants is given once a week with a concentration of 0 cc.l-1 5 cc.l-1, cc.l-1, 15 cc.l-1, 20 cc.l-1, 25 cc.l-1, 30 cc.l-1, cc.l-1, compost 150 g, but also need to be given artificial fertilizers such as NPK pearls with a concentration of 1,5 g per polybag every month up to 6 times giving. The results showed that the concentration of bioboost 30 cc.l-1 gave the highest fresh weight of 90,71 g which increased by 85,46% compared to the lowest yield of fresh weight above ground without giving bioboost (B0) which is 48, 91 g. The increase in fresh weight above ground level in the 30 cc.l-1 bioboost concentration treatment also gave the highest yield of 330,15 g, which caused an increase in fresh fruit weight per chili plant by 68,15 g, when compared to the lowest yield of fresh fruit planting without bioboost (B0) which is 196,34 g.